Comparison of Different Wheat Varieties Grown in Punjab for Leavened Flat Bread (Naan) Production - Amjad, Muhammad; Safdar, Muhammad Naeem; Mumtaz, Amer; Naseem, Khalid; Raza, Saeeda; Khalil, Samina (Pakistan Journal of Nutrition, 2010)
Seven wheat varieties i.e. Inqulab 91, Bhakkar 2002, AS 2002, Shafaq 2006, Sehar 2006, Auqab 2000 and GA 2002 collected from different locations of Punjab were subjected to physicochemical, rheological, minerals (copper, manganese, iron, zinc) and sensory analyses to determine their suitability for leavened flat bread (naan) preparation. Naans were prepared from different wheat flours and evaluated for colour, taste, flavor, texture, chewing ability, folding ability and overall acceptability. It was observed that Shafaq 2006 had the highest test weight (81.50 kg/hl), thousand kernel weight (41.20 g), zinc (8.50 mg kg-1) and lowest broken/shrunken grains (0.79%), insect damaged grains (0.45%), moisture (12.92%) and dough stability (4.11%), Bhakkar 2002 had the maximum broken / shrunken grains (1.61%), ash (0.61%), falling number (432) and minimum water absorption (54.05%), dough development time (2.21 min) and manganese (5.29 mg kg-1), whereas Sehar-2006 had the highest protein (10.84%), wet gluten (27.56%), dry gluten (9.35%), dough development time (4.12 min), copper (4.68 mg kg-1) and lowest edible foreign matter (0.42%), tolerance index (35.00 BU) and iron (14.80 mg kg-1). Naans prepared from Auqab 2000 were ranked highest and more acceptable than others.